Prognostic and predictive values of oncogenic BRAF, NRAS, c‐KIT and MITF in cutaneous and mucous melanoma. (26th January 2015) - Pracht, M.; Mogha, A.; Lespagnol, A.; Fautrel, A.; Mouchet, N.; Le Gall, F.; Paumier, V.; Lefeuvre‐Plesse, C.; Rioux‐Leclerc, N.; Mosser, J.; Oger, E.; Adamski, H.; et al.
Abstract Background Mutations of BRAF, NRAS and c‐KIT oncogenes are preferentially described in certain histological subtypes of melanoma and linked to specific histopathological features. BRAF‐, MEK‐ and KIT‐inhibitors led to improvement in overall survival of patients harbouring mutated metastatic melanoma. Objectives To assess the prevalence and types of BRAF, NRAS, c‐KIT and MITF mutations in cutaneous and mucous melanoma and to correlate mutation status with clinicopathological features and outcome. Methods Clinicopathological features and mutation status of 108 samples and of 98 consecutive patients were, respectively, assessed in one retrospective and one prospective study. Clinicopathological features were correlated with mutation status and the predictive value of these mutations was studied. Results This work identified significant correlations between BRAF mutations and melanoma occurring on non‐chronic sun‐damaged skin and superficial spreading melanoma (P < 0.05) on one hand, and between NRAS mutations and nodular melanoma (P < 0.05) on the other hand. Younger age (P < 0.05), microscopic (P < 0.05) and macroscopic (P < 0.05) lymphatic involvement at diagnosis of primary melanoma were significantly linked to BRAF mutations. A mutated status was a positive predictive factor of a response to BRAF inhibitors (OR = 3.44). Mutated melanoma showed a significantly (P = 0.038) higher objective response rate to cytotoxic chemotherapy (26.3%) than wild‐type tumours (6.7%). Conclusion Clinical and pathological characteristics of the primary melanoma differed between wild‐type and BRAF‐ or NRAS‐mutated tumours. Patients with BRAF‐mutated tumours were younger at diagnosis of primary melanoma. Patients carrying mutations showed better responses better to specific kinase inhibitors and interestingly also to systemic cytotoxic chemotherapy.